Ease or excitement? Exploring how concept stores contribute to a retail portfolio. Issue 7 (31st May 2021) - Egan-Wyer, Carys Jane; Burt, Steve; Hultman, Jens; Johansson, Ulf; Beckman, Alice; Michélsen, Clara
Abstract : Purpose: The study aims to explore how concept stores (theoretically) differ from other experience-based retail formats, and hence, how they (practically) contribute to a diversified retail store portfolio. Design/methodology/approach: Case study based on semi-structured, qualitative interviews with seven IKEA retail managers, three industry experts and 26 customers of IKEA concept stores in London and Stockholm. Findings: The concept store represents a conceptual departure from other experiential store formats. It is neither fully experiential in the sense that it is not only about marketing communications nor is it sales or profit-focused. Its aim is to be an accessible touchpoint that reduces friction on a diversified customer journey with its value to the retail portfolio being that it attracts new and latent customers, mitigates existing inhibiting factors and drives them to other touchpoints. Research limitations/implications: Ideas about the different characteristics of new store formats and their potential to shape the customer experience are extended. New formats reflect innovation in retailing and are part of a retail portfolio which generates different customer expectations and determinants from traditional store formats which provide the customers' existing reference point. Practical implications: The contributions of new formats should be evaluated in light of other existing formats in the portfolio and not isolated. This is particularly true when considering format cannibalisation and the potentially extended customer journey that arises when customers use traditional format stores and new concept format stores simultaneously. Originality/value: Previous research, using sales metrics and market-based results as performance determinants, suggests negative outcomes for format diversification. Our study suggests that the contributions of the concept store format should be viewed from an overall customer journey perspective and the "performance" of different format based touchpoints are not best captured through traditional sales evaluation methods.